Impact of ICT and Information Systems on Accounting Profession: a Study At Anan University, Nigeria - Sulaiman Taiwo Hassan; Egwuma Deborah Ojochenemi (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The relationship between ICT and the accounting profession in Nigeria is assessed in this study. A closed-ended, structured questionnaire was used as the research tool in this study and was given to the employees of the chosen businesses. The chi-square statistical tool, a non-parametric test used to ascertain whether a systematic link exists between two (2) variables, is used to assess the data acquired and retrieved from the research instrument used. The data analysis was conducted using the statistical package for social science (SPSS). According to the study's findings, there is a statistically significant correlation between ICT and the accounting profession in Nigeria. The research found that the accounting profession in Nigeria is impacted by the positive and robust relationship of ICT. A nation's rapid economic and social development is largely dependent on its ICT infrastructure, which has had an effect on the accounting profession in one way or another. Hajela (2005).This result is also consistent with Buseni James's (2023) discovery that workers' skills and ICT use are connected, indicating that companies with high ICT usage also employ more knowledge workers.